Pemenuhan Hak Kepemilikan Penerima Fidusia Terhadap Pemberi Fidusia yang Melakukan Wanprestasi Berdasarkan Akta Jaminan Fidusia - Andi Widjaja; Agus Salim; Belly Isnaeni (CV. ULIL ALBAB CORP, 2024)
This research discusses the legal consequences of the fiduciary grantor's default in the Fiduciary Guarantee Deed and the fulfillment of the fiduciary recipient's rights. The study employs a normative juridical approach with legislative, conceptual, and case methods, as well as a descriptive qualitative approach. The research analyzes data based on the theory of legal certainty, the theory of dispute resolution, and the theory of agreements. The high interest in credit among the public has led to the creation of fiduciary agreements, which achieve legal certainty when the Fiduciary Guarantee Deed is signed before a Notary and registered with the Ministry of Law and Human Rights. However, questions arise regarding the rights of the fiduciary recipient if the Fiduciary Guarantee Deed is not registered. The deed stipulates that if the Debtor or Fiduciary Grantor defaults or is negligent and does not rectify the negligence or fulfill obligations after being given a written notice, such negligence is sufficient evidence of default. The Fiduciary Grantor's right to the Collateral Object ends. The fulfillment of the fiduciary recipient's rights over a defaulting fiduciary grantor can be achieved through agreed stages or by referring to the principal agreement.